Do amor romântico ao poliamor: uma análise crítica a partir da teoria feminista - Silva, Graziele Campos da (2017)
The polyamorist proposal defends "new" ways to establish relationships, aiming nonhierarchical interactions and mutual cooperation, seeking to guarantee women sexualaffective freedom, assuming that monogamy is a prison and that romantic love must be fought. To distinguish itself from the other modalities of open relationship throughout history and the open relations of contemporaneity, the polyamory puts emphasis on love. Other highlights include freedom, equality, negotiation and communication. The aim of this work is to locate the discourse of romantic love within the polyamorist narrative, based on the analysis of feminist theory, starting from the questioning: Does polyamor practice disrupt romantic love? There are two axes that lead us to consider that it doesn’t: love remains at the center of the project of women’s life and there is no equality in relationships. This is a qualitative research, based on the follow-up of the virtual groups of discussion of Facebook, participant observation in group "Poliafetividade" and the analysis of four in-depth interviews of polyamorist women